Elevated Gut Microbiome-Derived Propionate Levels Are Associated With Reduced Sterile Lung Inflammation and Bacterial Immunity in Mice - Tian, Xiaoli; Hellman, Judith; Horswill, Alexander R.; Crosby, Heidi A.; Francis, Kevin P.; Prakash, Arun (Frontiers in Microbiology, 2019)
Short-chain fatty acids (SCFA) are important dietary and microbiome metabolites and have roles in gut immunity as well as distant organ function. We previously observed that gut microbiome alteration via antibiotics led to attenuated lung inflammatory responses. The rationale for this study was to identify gut microbiome factors that regulate lung immune homeostasis. We first investigated key factors within mouse colonic lumen filtrates (CLF) which could cause direct inflammatory effects in vitro. We identified LPS and SCFAs as key CLF ingredients whose levels and inflammatory capacity changed after antibiotic exposure in mice. Specifically, the SCFA propionate appeared to be a key regulator of LPS responses in vitro and propionate:acetate ratios within in vivo derived CLF correlated with observed in vitro responses. In vivo, exposure of lungs to high dose propionate, to mimic how prior antibiotic exposure changed SCFA levels, resulted in diminished immune containment of S.aureus pneumonia. Finally, we discovered an enrichment of propionate-producing gut bacteria in mice with reduced lung inflammation following lung ischemia reperfusion injury in vivo. Overall, our data show that propionate levels can distinctly modulate lung immune responses in vitro and in vivo and that gut microbiome increased production of propionate is associated with reduced lung inflammation.